2022
DOI: 10.1007/s11262-022-01896-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of plant transcriptomes reveals five putative novel poleroviruses and an enamovirus

Abstract: Transcriptome datasets available in public domain serve as valuable resource for identi cation and characterization of novel viral genomes. Poleroviruses are economically important plant-infecting RNA viruses belonging to the family Luteoviridae. In the present study, we explored the plant transcriptomes available in public domain and identi ed ve putative novel poleroviruses tentatively named as Foeniculum vulgare polerovirus (FvPV), Kalanchoe marnieriana polerovirus (KmPV), Paspalum notatum polerovirus (PnPV… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…He et al [ 21 ] recently reported that they identified 102 mammalian-infected viruses in 1941 game animals, with 65 described for the first time. In plant viruses, Sidharthan et al [ 22 ] previously reported the identification of five putative novel poleroviruses and an enamovirus through plant transcriptomes.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [ 21 ] recently reported that they identified 102 mammalian-infected viruses in 1941 game animals, with 65 described for the first time. In plant viruses, Sidharthan et al [ 22 ] previously reported the identification of five putative novel poleroviruses and an enamovirus through plant transcriptomes.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of Next Generation Sequencing (NGS) technologies has led to the increased deposition of transcriptomic reads and transcriptome-assembled contigs in public domain databases like Short Read Archives (SRA) and Transcriptome Shotgun Assembly (TSA), respectively of National Centre for Biotechnology Information (NCBI) (Kavi Sidharthan et al, 2022). As the original researches generating the transcriptome data are not 'virome-centric', viral sequences that might be present in those data often go unnoticed.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, viral taxonomy is witnessing a shift from the traditional taxonomy to the sequence-based taxonomy, which advocates the inclusion of viral sequences known only from metagenomic data in the International Committee on Taxonomy of Viruses (ICTV) taxonomy scheme for comprehensively characterizing global virome [5]. The acceptance of sequence-based viral taxonomy paved way for data-driven virus discovery studies that identi ed several putative novel plant viruses in various plant transcriptomes [6,7,8,9,10,11,12]. Thus, in the present study, we explored the transcriptome datasets of G. sylvestre available in public domain for novel plant viral sequences and identi ed a putative novel cholivirus.…”
Section: Introductionmentioning
confidence: 99%